Microbial plant pathogens-detection and disease diagnosis bacterial and phytoplasmal pathogens, vol.2 - Narayanasamy, P. (Springer, 2011)
The bacterial and wall-less phytoplasamal pathogens are comparatively much smaller than fungal pathogens. The morphological characteristics of bacterial pathogens have limited application for their detection and identification. Hence, cultural, biochemical and physiological characteristics have to be determined for the detection and identification of bacteria up to generic/species level. Immunoassays have been shown to be highly efficient for detection, identification and differentiation of isolates, strains and/ or pathovars of bacterial species. Application of various nucleic acid-based techniques based on hybridization of probes with complementary sequences of target bacterial pathogen DNA and / or amplification of unique sequences of the target bacterial species has been demonstrated to yield reliable and reproducible results rapidly. The nonculturable phytoplasmas have to be detected in plants, planting materials and the vectors involved in the transmission of these disease-causing agents from plant to plant. They have been identified and classified primarily based on the techniques based on the genomic nucleic acid characteristics. The comprehensive information presented in this volume, following extensive literature search is aimed to provide all that is required by the researchers, teachers and students of various disciplines of biological sciences, in addition to the extension pathologists, and personnel of plant quarantines and certification programs. The inclusion of a wide range of protocols is the unique feature of this volume enabling the scientists to choose the methods for their investigations.